Complex evaluation of structural state degree of strengthening nanocoatings - Skoblo, T.S.; Romaniuk, S.P.; Sidashenko, A.I.; Taran, V.S.; Taran, A.V.; Dorozhko, I.I.; Pilgui, N.N. (Вопросы атомной науки и техники, 2019)
The degree of structural heterogeneity of TiN coatings on the surface of cold-rolled 65 G thin sheet steel obtained in standard PVD and RF modes was investigated using the optical-mathematical method. The factors such as the diffusion of chemical components, the density of the structure and the intensity of the resulting deformations that affect the stability of the tool during operation are estimated.